Empowering Students Disaster Literacy: An Effort to Decrease Disaster Risk towards Reading Aloud Strategy - Rahayu Prasetyaningsih; Andi Mappewali; Andi Naniwarsih (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
This study aimed to prove whether the Reading Aloud Strategy can empower the disaster literacy of Al-Khairaat II Junior High School students. This research design is pre-experimental, in which researchers use one pretest-posttest group. The characteristic of this design is that it can only have pre-test and post-test groups without a control group. The sample of this study was students of class VIIIB of Al-Khairaat II Junior High School, Palu, a total of twenty people. The results of the data analysis showed that the alternative hypothesis is accepted, proving that the mean value of the post-test is greater than the mean value of the pre-test. In addition, the t_count value (4.7) is higher than the t_table value (2.024) with a significance level of 0.05 and (20-1) degrees of freedom (df). It is proven that the Reading Aloud strategy can improve the disaster literacy reading skills of students in class VIIIB of SMP Al-Khairaat II Palu.